2020
DOI: 10.1007/s40430-019-2166-0
|View full text |Cite
|
Sign up to set email alerts
|

A bottom-up approach to experimentally investigate the deposition of austenitic stainless steel in laser direct metal deposition system

Abstract: Direct metal deposition (DMD) is a method of metallic part fabrication under the classification of additive manufacturing process. In DMD, parts are manufactured by melting powder particles reaching the deposition zone, layer by layer with a laser beam. This potential process promises manufacturing flexibility of complex shapes deposition with a range of challenging materials. The work presents the establishment of laser, powder and deposition parameters in a newly developed metal-based direct laser deposition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 36 publications
(50 reference statements)
0
9
0
Order By: Relevance
“…Also, gradually the layers were seen to be bent through the middle. Due to this effect gradual reduction of laser power is advised by many researchers [6,10,28,29]. By manually reducing power by 100 W with each successive layer (Fig.…”
Section: Geometrical Feature Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Also, gradually the layers were seen to be bent through the middle. Due to this effect gradual reduction of laser power is advised by many researchers [6,10,28,29]. By manually reducing power by 100 W with each successive layer (Fig.…”
Section: Geometrical Feature Analysismentioning
confidence: 99%
“…The fabrication of such thin-walled structures is quite challenging due to complex stress distribution [5]. Also, it is often of interest to know the smallest possible feature which is geometrically consistent to be manufactured by DED [6]. Effective control of process parameters such as scan speed, laser speed, feed rate etc.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 Among them the well-known metal deposition processes of AM are DED and PBF. 36 However the limitations associated with these AM methods are low deposition rates and high equipment cost. 7 An aspiring method to process metal is the material extrusion, which is commonly known to handle materials like polymers.…”
Section: Introductionmentioning
confidence: 99%
“…The formation of macrocracks was fixed upon deposition with the minimum of excess, whereas only microcracks were observed when it increased. Pant et al [ 27 ] defined and discussed the geometrical characteristics and mechanical properties of single-layer and multi-layer walls when DMD processing with a coaxial-powder flow of 316 L steel, depending on the laser power, the laser spot speed, the intensity of the powder feeding, and overlapping factors. Ni et al [ 28 ] researched the influence of coaxial nozzle parameters on gas flow and the powder distribution on the surface formed by the DMD method and showed that the correct choice of these parameters ensures good morphology and quality of the deposited layer.…”
Section: Introductionmentioning
confidence: 99%